The BEPS Project of the OECD and the International Tax Law in Brazil - Rocha, Sergio André (2016)
In this article, the author analyzes the BEPS project of the OECD and its implications in the International Tax Law of Brazil as a potential generator of a new stage in the international taxation. In that sense, he explains the Brazilian international policy, the context that led the signing of conventions and the model that was followed for it. Furthermore, he assesses the importance of the fiscal transparency and the exchange of information, aspects connected with the cooperation and competition.